EFIKASI DIRI SISWA MELALUI LEMBAR KERJA PESERTA DIDIK BERBASIS TINJAUAN EMPIRIS TEORETIS - Rosdiana, Silvi Rosiva; Wulandari, Siska Ayu; Susanti, Indri; Aisyurrahman, Dimas Fahmi; Setiawan, Anhar (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2022)
The same thinking or giving the exact solution when expressed by several students in open-ended questions or High Order Thinking Skills (HOTS) indicates a lack of self-efficacy. This is the background of the purpose of this study to measure self-efficacy through Student Worksheets based on empirical and theoretical reviews on static fluid materials. This study is quasi-experimental because it uses a pre-post-test control group design. Sampling will be done using a purposive sampling technique. The samples were junior high school students in one of the Lamongan districts. The results of this study indicate that the Student Worksheet based on the theoretical, empirical review can increase students’ self-efficacy. An increase in self-efficacy was observed from the average value at the time of the pre-test, 62.68%, to 71.95% at the time of the post-test. The results of these values are classified as good improvement according to the Likert scale. Self-efficacy is measured using six indicators (scientific content, problem-solving ability, laboratory usage, daily application, scientific communication, and scientific literacy). Scientific literacy indicators get the lowest average value caused by the low interest of students in learning a concept. Therefore, it is necessary to conduct further research on the relationship between student interest and self-efficacy.